Desain Band Pass Filter pada Frekuensi X-Band Menggunakan Metode Square Resonator untuk Aplikasi Radar Navigasi - Trisa Mira; Sutrisno; Hanny Madiawati (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
A bandpass filter is a component that can pass signals within a certain frequency range, bandpass filter will pass frequencies that are within the cut-off frequency range and reduce frequencies that are outside the cut-off frequency range. A bandpass filter can be used as a component in a navigation radar system in its application. The navigation radar works on X-band frequency, so we need a bandpass filter that can work at the X-band frequency, where in addition to passing the desired frequency and dampening unwanted frequencies, the bandpass filter can also prevent interference that can occur in the modulation process on the radar system. So in this study, a bandpass filter type filter that works at the X-band frequency with a center frequency of 9,1 GHz will be designed, where this filter will be created using the square resonator method, the advantages of this method in addition to its dimensions and simple circuit, the resonator with the shape square will have a suitable bandpass filter response. The final optimization filter that has been carried out produces parameters including the center frequency which is at 9,1 GHz, the bandwidth is 1.5 Ghz, S1.1 is 2,6 dB, and S2.1 is 14.4 dB.